2014
DOI: 10.1007/s12639-014-0420-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastro-intestinal parasitic infections in goat of Madhya Pradesh, India

Abstract: Gastrointestinal (GI) parasitism in animals is one of the major problems in India causing emaciation, anaemia, oedema, weakness, diarrhoea and death. Present study was designed to generate epidemiological data on GI parasitism of goats of Madhya Pradesh, India. During 8 months study period, a total of 960 samples were collected and examined by sedimentation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 8 publications
10
31
2
Order By: Relevance
“…and the prevalence was 2.1%. Singh et al (2015) observed 3.1% infection in India which supported the findings of this study. Lower prevalence of Moniezia spp.…”
Section: Resultssupporting
confidence: 90%
“…and the prevalence was 2.1%. Singh et al (2015) observed 3.1% infection in India which supported the findings of this study. Lower prevalence of Moniezia spp.…”
Section: Resultssupporting
confidence: 90%
“…The present high overall prevalence of GIP infection obtained from fecal examination (89.33%) reflects the infection intensity among goats in Giza Governorate, Egypt. This result may be in accordance with those obtained by Singh et al (2015) and Jena et al (2018) who found that the prevalence of GIP infection was 86.13% in and around Ranchi, Jharkhand, India, and 94.48% in Madhya Pradesh, India, respectively, while Negasi et al that enteric protozoal infections contribute heavily in the parasitic load among the examined goats. Coccidian infection was the most prevalent GIP, it was reached 76.89%.…”
Section: Discussionsupporting
confidence: 92%
“…Coccidian infection was the most prevalent GIP, it was reached 76.89%. These results agreed with the findings of Lloyd and Soulsby (1978), Penjhorn et al (1994), Parihar et al (1996), Obijiaku and Agbede (2007), Jatau et al (2011), Singh et al (2015), Verma et al (2018) who reported high incidence of coccidian infection. In the current investigation, no pure infection of Eimeria spp.…”
Section: Discussionsupporting
confidence: 91%
“…in this study is 11.11% shows relatively close to the study found in India (Yadav et al, 2005;Bhat et al, 2014;Singh et al, 2014), prevalence rate of Trichuris sp. found 13.33% in my study similar to prevalence found in West Harerghe Zone (Kaur andKaur 2008, Tariq et al, 2008;Daniel et al, 2014).…”
Section: Discussionsupporting
confidence: 88%